Tugas dan Fungsi DPRD Kabupaten Sidoarjo dalam Menampung dan Menyalurkan Aspirasi Masyarakat Secara Efektif - Nabilah Shafa Rofiah; Galih Wahyu Pradana (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study aims to analyze the role of the Regional House of Representatives (DPRD) of Sidoarjo Regency in collecting public aspirations as part of local democratic practices. As a legislative body, DPRD holds the responsibility of absorbing and responding to public input through mechanisms such as reses, community meetings, and digital platforms. Using a descriptive qualitative approach, data were gathered through interviews, observations, and documentation. The findings indicate that although DPRD has established formal systems for collecting public input, their implementation remains suboptimal. Challenges include limited access for communities in remote areas, a lack of initiative from legislators in establishing active communication, and weak follow-up on collected aspirations. Many public inputs are documented but fail to influence concrete policy decisions, resulting in the erosion of public trust in the legislative process. Furthermore, the study highlights that the aspiration-gathering process often lacks transparency, and community participation is frequently symbolic rather than substantive. This disconnect between the DPRD and constituents undermines the legitimacy of local policymaking. To address these issues, the study recommends that DPRD optimize the use of digital media and outreach programs to bridge communication gaps, particularly in underserved areas. In addition, there is a need to institutionalize follow-up mechanisms that ensure public input is not only recorded but also translated into meaningful action plans or policy recommendations. Strengthening internal capacity, increasing public access to legislative activities, and promoting accountability are essential steps toward a more responsive and inclusive governance system. These efforts are crucial to support the development of public policies that are participatory and aligned with the real and diverse needs of Sidoarjo residents. Future research is suggested to evaluate the long-term impact of such reforms on public satisfaction and trust in legislative institutions.